Timing of and outcomes after selective termination of anomalous fetuses in dichorionic twin pregnancies†. (30th September 2014) - Bigelow, Catherine A.; Factor, Stephanie H.; Moshier, Erin; Bianco, Angela; Eddleman, Keith A.; Stone, Joanne L.
ABSTRACT Objective The objective of this article is to determine if selective termination (ST) of an anomalous dichorionic twin at early gestational age (GA) is associated with a decreased risk of fetal loss and prematurity. Method All patients who had ST for dichorionic twin pregnancies from 2004 through 2010 at Mount Sinai Medical Center were included. Data were collected via chart review and patient interview. Two case–control analyses were carried out: first, cases were nonviable deliveries, and controls were live births; and second, cases were live births <37 weeks' GA, and controls were live births ≥37 weeks' GA. Univariable and then multivariable analyses identified characteristics associated with pregnancy loss and prematurity. Results Among 80 participants, there were four (5%) fetal losses and 15 (19%) premature births. GA at ST was the only characteristic associated with pregnancy loss in multivariable exact logistic regression [OR = 1.43, 95% CI (1.03, 2.26), P = 0.03]. GA at ST was the only characteristic associated with premature delivery in multivariable exact logistic regression [OR = 1.18, 95% CI (1.02, 1.37), P = 0.03]. Conclusion This study suggests that ST performed earlier in pregnancy is associated with decreased fetal loss and prematurity. © 2014 John Wiley & Sons, Ltd.